Italian Public Opposes NATO Airstrikes. - United States Information Agency. Office of Research and Media Reaction. (Tufts University. Tisch Library., 2019)
Italian bases are the launching pad for most of the NATO aircraft being used in airstrikes against the Federal Republic of Yugoslavia. A flash USIA survey conducted in Italy after the start of NATO airstrikes (March 26-28) finds that - in contrast to the French and German publics - the Italian public opposes the current NATO operation in Kosovo. However, if the violence continues, more Italians may support military action.; Opinion Analysis M-56-99